STAGES OF DEVELOPMENT OF MODERN RUSSIAN LINGUISTICS: THEORETICAL AND APPLIED ASPECTS - Mukaddas Raufovna Yusupova (Web of Journals Publishing, 2025)
This thesis analyzes the stages of development of modern Russian linguistics, its scientific and theoretical foundations, and directions of practical application. It highlights the most pressing issues in contemporary linguistics, new methodological approaches, the formation and development trends of fields such as computational linguistics, corpus linguistics, pragmalinguistics, and sociolinguistics. The paper also examines practical aspects of learning, teaching, and translating the Russian language, as well as key principles of linguodidactics.
Keywords: Russian linguistics, cognitive linguistics, digital transformation of language, language norms, artificial intelligence, interference.